(untitled) (Studia Iberystyczne, 2014)
PREFIXED IRREGULAR VERBS IN PORTUGUESE AND OTHER ROMANCE LANGUAGES In Portuguese, as well as in other Romance languages, certain forms of some prefixed irregular verbs become regular. In the case of certain verbs, a parallel phenomenon has occurred in several Romance languages, in which the prefixed verb differs from the primary verb in its conjugation. There are also cases when Portuguese has a prefixed verb with regularization and other Romance languages have two different verbs, because there was a split in the evolution of the latin verb. Regularization occurs when there is a considerable semantic distance between the prefixed verb and the simple one.